80.6k views
0 votes
-8(x-3y) when x=-2 and y=-4

2 Answers

2 votes
-8(x-3y) when x=-2 and y=-4. To solve the answer, we need to do like this
-8(x-3y)
Substitute x with -2 and y with -4
-8[-2-3(-4)]
=-8(-2+12)
=-8(10)
=-80
Or
-8(x-3y)
Use distributive property
-8(x)-8(-3y)
=-8(x)+24(y)
Substitute x with -2 and y with -4
-8(-2)+24(-4)
=16-96
=-80. As a result, the correct answer is -80. Hope it help!
User Kanlukasz
by
8.1k points
3 votes
First let's put in the values.

-8(-2-3·-4)

Solve using PEMDAS

Parentheses (Multiplication)

-8(-2+12)

Parentheses (Addition)

-8 · 10

Multiplication

-80

The answer is -80
User Graykos
by
6.8k points